Asuhan Kebidanan Komprehensif pada Ny.I Umur 23 Tahun G2P1A0 di Puskesmas Penajam - Agustina; Luvi Dian Afriyani (Universitas Ngudi Waluyo, 2024)
Continuity of care is the provision of obstetric care starting from pregnancy, childbirth, postpartum, neonate to deciding to use a family with family (KB).This is intended as an effort to help, monitor, and detect the possibility of complications who accompany the mother and baby from pregnancy to the mother using birth control.The method of midwifery care at PKM Penajam is through home visits by providing counseling according to the needs of mothers. The obstetric care given to Mrs.